Using IoT technology for monitoring Alzheimer’s and elderly patients - Aseel Thamer Ebrahem; Marwa Mawfaq Mohamedsheet Al-Hatab; Entisar Younis Abd Al-Jabbar; Warqaa H. Alkhaled; Zaid Husham Al-Sawaff (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Alzheimer’s disease (AD) is a neurological disorder that results in the death of brain cells, causing memory loss, behavioral changes, and cognitive impairment. It drastically affects the individual’s work and social life, often leading to death, and is now the sixth leading cause of mortality worldwide. AD patients have limited mobility, which restricts their movement outside their homes. Thankfully, new internet of things (IoT) applications have made it possible to monitor people with various illnesses in their everyday lives, providing valuable assistance to caregivers. This study aims to create an IoT prototype that can locate an AD patient in real time and remind them to take their medication on schedule via an alarm. The small, lightweight, portable patient carrier has a NodeMCU-23DSP board, a Neo-06 global positioning system (GPS) module, and a wireless modem/Wi-Fi router. Remote patient follow-up through the Blynk 2.0 application on computers and Android devices allows for monitoring of the patient’s medication regimen and daily activities. As AD patients struggle with memory and organization, the prototype’s design enables monitoring of a patient’s course of medication, making it easier for caregivers to provide the necessary assistance. The prototype was tested to demonstrate its efficiency and performance.